Therapeutic evolution in HR+/HER2- breast cancer: from targeted therapy to endocrine therapy - Cao, Lu-Qi; Sun, Haidong; Xie, Yuhao; Patel, Harsh; Bo, Letao; Lin, Hanli; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2024)
Breast cancer, a complex and varied disease, has four distinct subtypes based on estrogen receptor (ER) and human epidermal growth factor receptor 2 (HER2) levels, among which a significant subtype known as HR+/HER2-breast cancer that has spurred numerous research.The prevalence of breast cancer and breast cancer-related death are the most serious threats to women's health worldwide. Current progress in treatment strategies for HR+/HER2-breast cancer encompasses targeted therapy, endocrine therapy, genomic immunotherapy, and supplementing traditional methods like surgical resection and radiotherapy. This review article summarizes the current epidemiology of HR+/HER2-breast cancer, introduces the classification of HR+/HER2-breast cancer and the commonly used treatment methods. The mechanisms of action of various drugs, including targeted therapy drugs and endocrine hormone therapy drugs, and their potential synergistic effects are deeply discussed. In addition, clinical trials of these drugs that have been completed or are still in progress are included.